Dioxirane-mediated Metal-free Oxidations of Target Molecules Containing Unsaturated Carbons - D’Accolti, Lucia; Annese, Cosimo; Fusco, Caterina (Current Organic Chemistry, 2015)
A remarkable example of the progress in metal-free oxidation is the development of oxidation with dioxiranes. The reactivity of these peroxides seems to be due to the tendency for easy electrophilic O-atom transfer to nucleophilic substrates. This has been applied in order to achieve high regio- and stereoselective epoxidation and oxyfunctionalizations of target molecules. This review addresses a new approach consisting of the application of homogeneous and heterogeneous dioxiranes isolated and generate in situ. This method has shown promise to contribute to resolving a well-recognized general problem in the organic synthesis to achieve efficient synthetic methods that take into account the fundamental principles of green chemistry.
Keywords: metal free oxidation